Peranan Set Elemen Panggung Teater Realis Pada Interior “Bunga Rumah Makan” dan “Operasi” Gedung Pertunjukkan Sawunggaling Universitas Negeri Surabaya - Olivia Setiya Budi; martino dwi nugroho; Poppy Firtatwentyna Nilasari (Intra, 2014)
The emergence of theater community and arts institution in Indonesia proved that the development of the art of drama/theater is growing. The community is able to deliver good performances, mature and both visually. This research to determine the set of stage elements that are applied to the staging platform